RESPON PUPUK KANDANG AYAM DAN NPK TERHADAP PERTUMBUHAN DAN HASIL TERONG UNGU - saijo, saijo saijo (Universitas Lambung Mangkurat, 2025)
The purpose of the study was to test and analyze the response of chicken manure and NPK 16:16:16 application on the growth and yield of purple eggplant plants in sandy land. The study used a Randomized Bloc Design, consisting of two factors. The first treatment was the provision of 4 levels of chicken manure with doses of 0, 30, 35 and 40 t ha-1 while the second treatment of NPK 16:16:16 consisted of 3 levels, namely doses of 0, 300 and 350 kg ha-1. From the two treatment factors, 12 combinations were obtained. Each was repeated 3 times, so that there were 36 experimental units. The results showed that the response of chicken manure affected all growth variables, both plant height, stem diameter and number of productive branches at a dose of 30 t ha-1. While the dose of 40 t ha-1 affected the yield variable in the form of the number of fruits per plant with the largest number of 8 fruits per plant with the heaviest fruit weight of 223.89 g fruit-1. In addition, the dose response of NPK 16:16:16 also affects the yield variable in the form of the number of fruits per plant at a dose of 350 kg ha-1 with the largest number of fruits being 6 fruits per plant-1.